THE IMPACT ANALYSIS OF VARIOUS BUDGET MANAGEMENT SYSTEMS IN ESTABLISHING SUSTAINABLE HYDROGEN SUPPLY CHAIN IN CENTRAL ASIA - Nuraliyeva Komila Sanakulovna (Web of Journals Publishing, 2025)
The emergence of hydrogen as a key element in the global green transition has sparked interest in developing sustainable hydrogen supply chains, especially in regions with high renewable energy potential such as Central Asia. However, the realization of this potential is closely tied to how public resources are managed and allocated. This study investigates the role of different budget management systems—namely traditional, program-based, and performance-based budgeting—in facilitating the establishment of a sustainable hydrogen supply chain in Central Asia. The analysis focuses on how these systems influence investment planning, inter-sectoral coordination, financial transparency, and long-term policy implementation. Through a comparative evaluation of budgetary practices in Kazakhstan, Uzbekistan, and Turkmenistan, the study identifies critical enablers and bottlenecks within each system. The findings underscore that transitioning to modern, performance-oriented budgeting models is essential to attract investment, ensure accountability, and support green infrastructure development, ultimately accelerating the region’s transition to a hydrogen-driven energy future.
Keywords: Hydrogen supply chain, budget management systems, sustainable energy, performance-based budgeting, program-based budgeting, Central Asia, green hydrogen, public finance, renewable energy investment, fiscal policy